Atletas y equipos deportivos como sistemas adaptativos complejos: Una revision de las Implicaciones para el diseño del aprendizaje - Davids, K. (Revista Internacional de Ciencias del Deporte, 2015)
Ecological dynamics is a systems-oriented theoretical framework which conceptualises sport performers as complex adaptive systems. It seeks to understand the adaptive relations that emerge during coordination of interactions between each performer and a specific performance environment. This approach has identified the individual-environment relationship as the relevant scale of analysis for explaining how processes of perception, cognition and action underpin expert performance in sport. This theoretical overview elucidates key ideas from previous work identifying functional characteristics of complex adaptive systems, such as co-adaptation, emergent coordination tendencies and capacity to utilise affordances, which underlie performance and learning in team and individual sports. The review of research focuses on how key principles of ecological dynamics inform our understanding of learning and transfer, and their impact on practice task design in sport development programmes. To support this analysis, data from research on performance of elite and developmental athletes in individual and team sports are presented to highlight important principles of learning design from an ecological dynamics perspective.